Psychometric properties of the job anxiety scale - Schmalbach, Ileana; Schmalbach, Bjarne; Kalkbrenner, Andreas; Bassler, Markus; Hinz, Andreas; Petrowski, Katja (Frontiers in Psychology, 2023)
Background: Occupational stress and specifically job anxiety are crucial factors in determining health outcomes, job satisfaction as well as performance. In order to assess this phenomenon, the Job Anxiety Scale (JAS) is one of the instruments available. It consists of 70 items that are clustered in 14 subscales and five dimensions. This manuscript is a revised version of a retracted article that analyzed the properties of a short version of the JAS. Rather than shortening the scale, Muschalla and colleagues recommend to further assess the scale in its current state without modification of the factor structure. Hence, the aim of this paper is to assess the psychometric properties of the original JAS. Methods: The sample consists of 991 – mostly psychosomatic – patients from two different clinics. We applied methods of factor analysis and bivariate correlations to explore and test factor structure and the nomological net of related constructs. Results: The Job Anxiety Scale evinced satisfactory psychometric properties. We found very high internal consistency, and invariance across participant age. It displayed good discriminant validity and we found the expected pattern of convergent correlations. However, the model fit is not convincing. Conclusions: With the Job Anxiety Scale, researchers can assess job related worries in a reliable manner. The questionnaire is particularly useful in large-scale surveys, in therapy or work-related contexts. However, the scale could be modified in order to aim for a better fit and assess job related anxiety in a more efficient way.